2022
DOI: 10.1515/mt-2021-2165
|View full text |Cite
|
Sign up to set email alerts
|

Laser and TIG welding of additive manufactured Ti-6Al-4V parts

Abstract: Electron beam melting (EBM) is a powder bed additive manufacturing (AM) technology for small and medium-sized Ti-6Al-4V components. In this study, EBM-built Ti-6Al-4V tensile specimens were joined using tungsten inert gas (TIG) welding and laser beam welding (LBW) to form large-scale components. Weld morphology, defects, mechanical properties, and microstructure of joints made by LBW and TIG welding were compared. It was found that the pore sensitivity of EBMed Ti-6Al-4V is extremely high. In EBM, the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Composites are widely used in aerospace, 1 automotive, 2 and industrial applications due to their high strengthto-weight ratio and excellent mechanical properties along with titanium. [3][4][5][6] Currently, micro-drilling of composites finds extensive application in various fields, including aircraft engine nacelle, and wind turbine blades in order to reduce noise which results in acoustic fatigue damage. [7][8][9] Mechanical drilling and laser drilling methods are common practices for fiber-reinforced composites and in some cases, combining these techniques allows for optimizing efficiency, balancing cost considerations with the need for precision in composite hole-making processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composites are widely used in aerospace, 1 automotive, 2 and industrial applications due to their high strengthto-weight ratio and excellent mechanical properties along with titanium. [3][4][5][6] Currently, micro-drilling of composites finds extensive application in various fields, including aircraft engine nacelle, and wind turbine blades in order to reduce noise which results in acoustic fatigue damage. [7][8][9] Mechanical drilling and laser drilling methods are common practices for fiber-reinforced composites and in some cases, combining these techniques allows for optimizing efficiency, balancing cost considerations with the need for precision in composite hole-making processes.…”
Section: Introductionmentioning
confidence: 99%
“…Composites are widely used in aerospace, 1 automotive, 2 and industrial applications due to their high strength‐to‐weight ratio and excellent mechanical properties along with titanium 3–6 . Currently, micro‐drilling of composites finds extensive application in various fields, including aircraft engine nacelle, and wind turbine blades in order to reduce noise which results in acoustic fatigue damage 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in greater tensile strength and hardness compared to low heat input. The weld seam morphology, defects, mechanical properties, and microstructure of deposits obtained by Electron Beam Melting (EBM), Tungsten Inert Gas (TIG), and Laser Beam Welding (LBW) of Ti-6Al-4V were compared [23,24]. The results revealed that internal defects in EBM Ti-6Al-4V samples produced during the manufacturing process were smaller than those occurring during the welding process.…”
Section: Introductionmentioning
confidence: 99%